Spiritual Journey and Behavior of the Santri as A Reflection of The Begawan in The Novel Kabar Buruk Dari Langit - Putra, Wahyu Kartika; Mukafi, Muhammad Hamdan (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
The world of santri has a relationship with the worldview in several literary works. The birth of writings that target the values of religiosity, especially those in the universe of the pesantren world, is a representation that cannot be ignored. Literary works that are present as an aesthetic also create a reflective bridge in the form of a worldview, including spiritual and religious elements. The novel Kabar Buruk dari Langit with a process raises the Begawan character who constructively accepts various definitions, which are not lost on him, especially his experience as a santri . Society sees the Begawan as a symbol that is both transcendental and decadent depending on what kind of society is judging him. The assessment mainly arises from other santri who seem to represent Begawan's behavior which has elements of Sufism in a contradictory perspectiveÂ